Karakteristik Tanah Gambut Transisi dan Gambut Pedalaman Kalimantan Selatan pada Tingkat Perombakan Hemik - Nurul Huda; Zuraida Titin Mariana; Hairil Ifansyah (Acta Solum, 2022)
Peat soil has various characteristics due to differences in peat-forming materials, formation processes, and environmental conditions. In South Kalimantan, the environment of peat formation is more dominant in the form of transition peat and inland peat. This study aims to determine the characteristics of transition peat soil and inland peat, including soil pH, total acidity, carboxylic functional groups (-COOH) and OH-phenolic functional groups, in South Kalimantan at the level of hemic reshuffle. This study used a purposive sampling method with regard to the decompotion degree of peat, i.e., hemic (half baked). The soil used comes from transitional peat (Sub-district of North Ulin/LUU and West Ulin Platform/LUB) and inland peat (Banjang District, Hulu Sungai Utara/HSU) and Kandangan Subdistrict, Hulu Sungai Selatan/HSS). The results showed that soil acidity in transitional peat (LUU and LUB) was higher than inland peat (HSU and HSS) as indicated by the pH value of transitional peat soil with a range of 4.25 and a total acidity concentration of 234.16 cmol kg-1 for transitional peat, while the carboxylic groups (-COOH) concentration in transition peat (LUU and LUB) and inland peat (HSU and HSS) showed almost the same concentration of 94.91 cmol kg-1 in transitional peat (LUU and LUB) and 92.83 cmol kg-1 in inland peat (HSU and HSS). The concentration of OH-phenolic groups in transitional peat (LUU and LUB) is higher than inland peat (HSU and HSS), which is indicated by the transitional peat OH-phenolic (LUU and LUB) groups concentration of 139.25 cmol kg-1.